Prevalence rate of Internet addiction among Japanese college students: Two cross‐sectional studies and reconsideration of cut‐off points of Young's Internet Addiction Test in Japan - Tateno, Masaru; Teo, Alan R.; Shiraishi, Masaki; Tayama, Masaya; Kawanishi, Chiaki; Kato, Takahiro A. (Psychiatry and clinical neurosciences, 2018)
Aim Due to variation in estimates of the prevalence of Internet addiction (IA) in prior research, we conducted two cross‐sectional studies over 2 years investigating the prevalence rate of IA in college students in Japan and reconsidered appropriate cut‐off points of a self‐rating scale to screen possible IA. Methods This study was composed of two parts: survey I in 2014 and survey II in 2016, which were conducted in the same schools with an interval of 2 years. The study questionnaire included questions about demographics and Internet use, and Young's Internet Addiction Test (IAT). Additionally, the subjects in survey II were asked about self‐reported IA. Results There were 1005 respondents in total with a mean age (± SD) of 18.9 ± 1.3 years. The mean IAT scores remained stable between 2014 and 2016: 45.2 ± 12.6 in survey I and 45.5 ± 13.1 in survey II (overall mean IAT score of 45.4 ± 13.0). With respect to self‐reported IA in survey II, a total of 21.6% admitted to having IA (score of 5 or 6 on a 6‐point Likert scale). We categorized these subjects as IA, and the remainder as non‐IA. The mean IAT score showed a significant difference between these two groups (57.8 ± 14.3 vs 42.1 ± 10.7, P < 0.001). Conclusion The severity of IA symptoms among Japanese college students has appeared stable in recent years, with mean IAT scores of over 40. Our results suggest that a screening score cut‐off of 40 on the IAT could be reconsidered and that 50 might be proposed for the cut‐off.